Microtubule-depolymerizing agents used in antibody-drug conjugates induce antitumor immunity by stimulation of dendritic cells - Müller, Philipp; Martin, Kea; Theurich, Sebastian; Schreiner, Jens; Savic, Spasenija; Terszowski, Grzegorz; Lardinois, Didier; Heinzelmann-Schwarz, Viola A; Schlaak, Max; Kvasnicka, Hans-Michael; Spagnoli, Giulio; Dirnhofer, Stephan; et al. (Cancer immunology research, 2014)
Antibody-drug conjugates (ADC) are emerging as powerful treatment strategies with outstanding target-specificity and high therapeutic activity in patients with cancer. Brentuximab vedotin represents a first-in-class ADC directed against CD30(+) malignancies. We hypothesized that its sustained clinical responses could be related to the stimulation of an anticancer immune response. In this study, we demonstrate that the dolastatin family of microtubule inhibitors, from which the cytotoxic component of brentuximab vedotin is derived, comprises potent inducers of phenotypic and functional dendritic cell (DC) maturation. In addition to the direct cytotoxic effect on tumor cells, dolastatins efficiently promoted antigen uptake and migration of tumor-resident DCs to the tumor-draining lymph nodes. Exposure of murine and human DCs to dolastatins significantly increased their capacity to prime T cells. Underlining the requirement of an intact host immune system for the full therapeutic benefit of dolastatins, the antitumor effect was far less pronounced in immunocompromised mice. We observed substantial therapeutic synergies when combining dolastatins with tumor antigen-specific vaccination or blockade of the PD-1-PD-L1 and CTLA-4 coinhibitory pathways. Ultimately, treatment with ADCs using dolastatins induces DC homing and activates cellular antitumor immune responses in patients. Our data reveal a novel mechanism of action for dolastatins and provide a strong rationale for clinical treatment regimens combining dolastatin-based therapies, such as brentuximab vedotin, with immune-based therapies.